Out‐of‐pocket spending among a cohort of Australians living with gout. (25th September 2020) - Nathan, Nicholas; Nguyen, Amy D.; Stocker, Sophie; Laba, Tracey‐Lea; Baysari, Melissa T.; Day, Richard O.
Abstract: Objective: To measure the direct and indirect out‐of‐pocket (OOP) costs borne by Australians with gout. Methods: A cross‐sectional, Australia‐wide, web‐based survey was conducted over 12 months between May 2017 and April 2018. Participants were recruited via advertisements in doctors' clinics and healthcare organizations' websites, and social media platforms such as Facebook and Twitter. Survey questions collected information about participants' OOP spending on direct medical and non‐medical gout‐related healthcare costs. Participant demographics, gout status, healthcare sought, workdays lost to due gout and health‐related quality of life were also collected. Results: Seventy‐nine patients with gout completed the survey; 70 (89%) were male, and on average were 56 (SD 16) years of age and had gout for 14 (SD 12) years. For this cohort, the median total OOP direct medical cost was AU$200 per year (interquartile range [IQR]: AU$60‐AU$570). Sixty (76%) people with gout reported being affected by gout during work; however, only 0.25 (IQR: 0‐3) days of work (approximately $60) were lost due to gout in a year. Nine percent (n = 7) of participants experienced cost‐related treatment attrition and 33% reported economic hardship (n = 26). Participants who experienced economic hardship or cost‐related treatment attrition had higher median total gout‐related direct costs than those who did not. Conclusion: In Australia, gout has an OOP financial cost and reduces work productivity. The presence of cost‐related treatment attrition among people with gout indicates that financial costs may be a significant barrier to seeking treatment for a subset of patients with gout.